Efficacy of Zinc Fortified and Fermented Wheat Flour (EZAFFAW): A randomized controlled trial protocol - Das, Jai K.; Padhani, Zahra Ali; Khan, Muhammad; Mirani, Mushtaq; Rizvi, Arjumand; Chauhadry, Imran Ahmed; Yasin, Rahima; Ismail, Tariq; Akhtar, Saeed; Begum, Kehkashan; Iqbal, Junaid; Humayun, Khadija; et al. (2024)
Background Zinc deficiency poses significant health risks, particularly in low-income settings. This study aims to evaluate the impact of agronomically zinc biofortified (fermented and non-fermented) and post-harvest wheat flour flatbread on zinc status and metabolic health in adolescents and adult women in rural Pakistan. Methods A four-arm triple-blind randomized controlled trial will be conducted in a rural district of Paki stan. Participants (adolescents aged 10–19 and adult women aged 20–40) will be assigned to receive fermented or unfermented high zinc agronomically biofortified wheat flour flat bread, post-harvest zinc-fortified wheat flour flatbread, or low zinc conventional whole wheat flour flatbread. The meal would be served once a day, six days a week for six months. The study aims to enroll 1000 participants and will be analyzed based on the intention-to-treat principle. The trial is registered with number NCT06092515. Outcomes Primary outcomes will include serum zinc concentration and metabolic markers, while secondary outcomes include anthropometric measurements, blood pressure, and dietary intake. Conclusion This trial will provide valuable insights into the efficacy of agronomically zinc biofortified wheat flour in improving zinc status and metabolic health. Findings may inform public health strategies to combat zinc deficiency in resource-limited settings.